Selective Air Oxidation of Bis- and Trisphosphines Adsorbed on Activated Carbon Surfaces - Ehsan Shakeri; John C. Hoefler; Janet Blümel (Molecules, 2025)
Bis- and trisphosphines incorporating methylene and aryl spacers readily adsorb on the surface of porous activated carbon (AC). The adsorption can be performed in the absence of solvents, even when the phosphines have high melting points, or from solutions. The diverse phosphines Ph2PCH2PPh2 (dppm), Ph2P(CH2)2PPh2 (dppe), Ph2P(CH2)3PPh2 (dppp), Ph2P(p-C6H4)PPh2 (dppbz), and (Ph2PCH2)3CCH3 (tdme) were adsorbed in submonolayers on AC. The adsorbed phosphines were studied by 31P MAS (magic angle spinning) NMR spectroscopy, and their mobilities on the surface were confirmed by determining the 31P T1 relaxation times. All phosphine groups of each bis- and trisphosphine molecule are in contact with the surface, and the molecules exhibit translational mobility as one unit. All phosphines used here are air-stable. Once a submonolayer is created on the AC surface, oxygen from the air is co-adsorbed and transforms all phosphines quantitatively into phosphine oxides at room temperature. The oxidation proceeds in a consecutive manner with the oxidation of one phosphine group after another until the fully oxidized species are formed. Studies of the kinetics are based on integrating the signals in the solution 31P NMR spectra. High temperatures and low surface coverages increase the speed of the oxidation, while light and acid have no impact. The oxidation is fast and complete within one hour for 10% surface coverage at room temperature. In order to study the mechanism and slow down the oxidation, a higher surface coverage of 40% was applied. No unwanted P(V) side products or water adducts were observed. The clean phosphine oxides could be recovered in high yields by washing them off of the AC surface. The oxidation is based on radical activation of O2 on the AC surface due to delocalized electrons on the AC surface. This is corroborated by the result that AIBN-derived radicals enable the air oxidation of PPh3 in solution at 65 °C. When the air-stable complex (CO)2Ni(PPh3)2 is applied to the AC surface and exposed to the air, OPPh3 forms quantitatively. The new surface-assisted air oxidation of phosphines adsorbed on AC renders expensive and hazardous oxidizers obsolete and opens a synthetic pathway to the selective mono-oxidation of bis- and trisphosphines.